THE RELATIONSHIP BETWEEN WORKLOAD, COMPETENCY AND MOTIVATION AND NURSE PERFORMANCE WITH REWARD AS AN INTERVENING VARIABLE IN MEDICAL INTENSIVE AND PEDIATRIC SURGERY UNIT & PJB HEART AND VASPHERE HOSPITAL JAKARTA - nurdin, neni aripiyanti (Lembaga Penerbitan Universitas Esa Unggul, 2023)
ABSTRACTIn the management of hospital management there are problems in terms of work performance of nurses contained in the nurse performance assessment (IKI) of nurses who are not optimal. This is allegedly influenced by various factors including workload, competence and motivation. So this study aims to describe, analyze, and determine the relationship of workload, competence and motivation with the performance of nurses with reward as an intervening variable in the Pediatric Medical and Surgical Intensive Unit & PJB Harapan Kita Cardiothoracic Hospital, Jakarta.This research is to analyze the problem, using 61 respondents. The research design is cross sectional. Data collection techniques used survey methods with descriptive analysis and questionnaires with a 5 Likert scale. Data analysis was performed by linear regression analysis.From the results of the study, (1) there is a jointly significant relationship between workload, competence, motivation, and nurse performance with reward as an intervening variable; (2) workload after being controlled by other variables has no significant relationship with nurse performance; (3) competence has a relationship with nurse performance; (4) motivation has a relationship with nurse performance; (5) rewards have a relationship with nurse performance; (6) workload has no relationship with reward; (7) competence has a relationship with rewards; (8) motivation has a relationship with rewards Keywords: Workload, competence, Motivation, Reward and Nurse Performance